Herpes simplex virus infection and propagation in a mouse L cell mutant lacking heparan sulfate proteoglycans. - Gruenheid, S (1993)
We have isolated a variant line of mouse L cells, termed gro2C, which is partially resistant to infection by herpes simplex virus type 1 (HSV-1). Characterization of the genetic defect in gro2C cells revealed that this cell line harbors a specific defect in the heparan sulfate synthesis pathway. Specifically, anion-exchange high-performance liquid chromatography of metabolically radiolabeled glycosaminoglycans indicated that chondroitin sulfate moieties were synthesized normally in the mutant cells, whereas heparin-like chains were absent. Because of these properties, we have used these cells to investigate the role of heparan sulfate proteoglycans in the HSV-1 life cycle. In this report, we demonstrate that the partial block to HSV-1 infection in gro2C cells occurs in the virus entry pathway. Virus adsorption assays using radiolabeled HSV-1 (KOS) revealed that the gro2C cell surface is a relatively poor target for HSV-1 in that virus attachment was 85% lower in the mutant cells than in the parental L cell controls. A portion of the 15% residual virus adsorption was functional, however, insofar as gro2C cells were susceptible to HSV-1 infection in plaque assays and in single-step growth experiments. Moreover, although the number of HSV-1 plaques that formed in gro2C monolayers was reduced by 85%, the plaque morphology was normal, and the virus released from the mutant cells was infectious. Taken together, these results provide strong genetic evidence that heparan sulfate proteoglycans enhance the efficiency of HSV attachment to the cell surface but are otherwise not essential at any stage of the lytic cycle in culture. Moreover, in the absence of heparan sulfate, other cell surface molecules appear to confer susceptibility to HSV, leading to a productive viral infection.